Microstructure analysis and permanent deformation of porous asphalt incorporating steel fiber - Anis Soraya, Mohd Rodzi; Khairil Azman, Masri; Md. Shahnewaz, Shoaib; Rashida, Ferdaus; Nadiatul Adilah, Ahmad Abdul Ghani; Ahmad Kamil, Arshad (IOP Publishing Ltd., 2024)
Porous asphalt mixture is primarily applied to the surface drainage layer of pavements due to its advantages in terms of noise reduction and protection during rainfall due to its open structure with high percentage of air void. This would allow the water to be stored and moved horizontally within the layer of the pavement. This can reduce splash and the spray effects which can increases driver’s visibility during rainfall. But, the high percentage of air void would give disadvantages to the porous asphalt such as rutting, cracking, and stripping. The objective of this study is to compare the microstructure of porous asphalt on a mixture that is contain 0% and 0.3% of additive which is steel fibre. The analysis includes getting images from Scanning Electron Microscope (SEM), Energy Dispersive X-ray (EDX), X-ray Diffractometer (XRD), and Fourier-Transform Infrared Spectroscopy (FTIR). The second objective is to evaluate permanent deformation of porous asphalt incorporating 0% and 0.3% of steel fibre. From the result, it shows that the addition of steel fiber can significantly enhance the properties of porous asphalt mixture.